Computational simulation of heat transfer enhancement by using nanofluid in a rectangular heated pipe / Houman Yarmand - Houman, Yarmand (2013)
Thermal characteristics of turbulent nanofluid flow in rectangular pipe are numerically investigated. The continuity, momentum and energy equations were solved by means of a finite volume method (FVM). The upper wall of channel is heated at constant heat flux while the bottom wall is symmetry, the left side is subjected to velocity inlet, and the right side of the channel is subjected to pressure outlet. Four different types of nanoparticles Al2O3, ZnO, CuO and SiO2 with different volume fractions in the range of 1% to 5% are used. In this project, effect of different Reynolds number in range of 5000 <Re <25000 were investigated to identify the effect on the heat transfer characteristics. The numerical results indicate that water-SiO2 has the highest Nusselt number compared with other nanofluids. The Nusselt number increases as the Reynolds number is increased .Similarly, the Nusselt number increases as the volume fraction is increased.